2012
DOI: 10.1080/10361146.2012.677002
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Change, Policy Issues and Voter Defection in the 2010 Australian Election

Abstract: Leadership change formed the backdrop to the 2010 Australian federal election, with the replacement of Kevin Rudd as Prime Minister by Julia Gillard, the country's first female Prime Minister. This article uses the 2010 Australian Election Study to examine patterns of voter defection between the 2007 and 2010 elections. The results show that the predominant influence on defection was how voters rated the leaders. Julia Gillard was popular among female voters and her overall impact on the vote was slightly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, a question in the AES about whether voters approved or disapproved of the move to replace Abbott revealed that a narrow majority disapproved (51 per cent, to 49 approved). This finding stands in contrast to when the Labor Party replaced Rudd with Gillard before the 2010 election, after which some three quarters of the AES sample disapproved (Bean and McAllister 2012). Table 10.6 looks in more detail at the images of the two main leadership rivals, Turnbull and Shorten.…”
Section: Perceptions Of Parties and Leadersmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, a question in the AES about whether voters approved or disapproved of the move to replace Abbott revealed that a narrow majority disapproved (51 per cent, to 49 approved). This finding stands in contrast to when the Labor Party replaced Rudd with Gillard before the 2010 election, after which some three quarters of the AES sample disapproved (Bean and McAllister 2012). Table 10.6 looks in more detail at the images of the two main leadership rivals, Turnbull and Shorten.…”
Section: Perceptions Of Parties and Leadersmentioning
confidence: 91%
“…The first variable in Table 10.3, gender, is a case in point. Over time, the so-called gender gap had virtually disappeared, but in 2010, when Australia's first female prime minister, Julia Gillard, contested the election, it reappeared, albeit with its direction reversed (Bean and McAllister 2012). In 2013, the gender gap closed up again (Bean and McAllister 2015), but in 2016 we see a pattern similar to that of 2010 in which women are more likely to support Labor than men (by 7 per cent) and also more likely to vote for the Greens than men (by 4 per cent).…”
Section: Social Background and The Votementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has also been documenting how voters have their own issue agendas, which may or may not coincide with the emphasis placed on these issues by the political parties during the election campaign (Goot and Watson 2007;McAllister, Bean and Pietsch 2012). Thus, health, education, economic management and taxation repeatedly feature as election issues of significance.…”
Section: Issues In the 2013 Electionmentioning
confidence: 99%
“…A growing body of research has also been documenting how voters have their own issue agendas, which may or may not coincide with the emphasis placed on these issues by the political parties during the election campaign (Goot and Watson 2007;Bean and McAllister 2012;McAllister, Bean and Pietsch 2012). Thus, health, education, economic management and taxation repeatedly feature as election issues of significance.…”
Section: Issues In the 2013 Electionmentioning
confidence: 99%